TEACHING VOCABULARY BY USING PUZZLE GAMES TO YOUNG CHILDREN AT POINT EDUCATION CENTER, LAWEYAN, SURAKARTA - Baehaqi, Muski (2007)
This study is aimed at describing the implementation of teaching vocabulary by using puzzle games, the problem faced by the teachers and the students, and the student’s response on the implementation of puzzle games in teaching vocabulary. The result of this study is expected to contribute the teaching learning English at the course particularly in vocabulary skill.